Spatial requirements of poultry assessed by using a colour-contrast method (KobaPlan). Issue 1 (2nd January 2016) - Spindler, B.; Giersberg, M. F.; Briese, A.; Kemper, N.; Hartung, J.
Abstract: Sufficient floor space is a fundamental precondition for poultry to perform normal behavioural patterns. To calculate and determine stocking densities, it is essential to know the absolute minimum surface area required by any given animal (body space). Additional space is required for characteristic behaviours (behavioural space) and for adequate inter-individual distances, group sizes and room to perform social interactions have to be taken into account. To calculate body space, planimetric measurements were carried out by the colour contrast method "KobaPlan" in various poultry species in standing and sitting positions and at a number of different ages. They included laying hens (Lohmann brown (LB), Lohmann selected Leghorn (LSL)), broiler breeders (Ross, both genders), broiler chickens (Ross 308, both genders), turkeys (BUT 6, males), Peking ducks (Cherry Valley, both genders) and Muscovy ducks (Canedins R51, males). Depending on live weight, age, plumage condition and body position, LB hens occupied an average area between 401 cm 2 and 542 cm 2, LSL hens between 353 cm 2 and 445 cm 2, broiler breeder females between 440 cm 2 and 537 cm 2, broiler breeder males 623 cm 2 up to 945 cm 2, broiler chickens up to 434 cm 2, male fattening turkeys up to 1808 cm 2, Muscovy drakes up to 873 cm 2 and Peking ducks up to 627 cm 2 . The values can be regarded as necessary minimum spatial requirements for the measured poultry species and genotype. The current method offers the potential to record the area occupied by animals exhibiting species-specific behavioural patterns.